Keragaman Bakteri Enterik Patogen Siput Felle (Angulyagra tricostata) dari Pesisir Danau Sentani Kabupaten Jayapura - Dais Iswanto; Daniel Lantang; Tri Gunaedi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2013)
Felle Snails (Angulyagra tricostata) is an alternative source of animal protein for the people around Sentani Lake. Meat of Felle snails has an indication of being contaminated by pathogenic enteric bacteria harmful to the health of the public consumption. The purpose of this study was to determine the diversity of bacterial enteric pathogens in Felle snails (A. tricostata) from the coast of Sentani Lake, Jayapura. Felle snails were taken from various points near existing residential areas around the coastal region of Sentani Lake. Extraction of meats Snail dilutions was made prior to planting in stages up to 10-10. Each serial dilution of 0.1 mL were taken and inoculated into Lactose Broth medium (LB), Mac Conkey Media (MC) agar and media EMBA at 370C for 24 hours. Colonies that grew were sub-cultured to get different colonies and grown on agar slant. Identification of individual characters was performed by colony fenetik numerical methods. The result indicated that there were seven selected isolates and the dendrogram showed that those species were similar to four of genus Enterobacteriaceae. Seven isolates consisted of 2 isolates similar to the genus Escherchiae, 2 isolates similar to Klebsiellae, 2 isolates similar to the genus Salmonellae and 1 isolate similar to the genus Shigellae. Similarity index value of each selected isolates ranged from 69 to 86%.Key words: Felle snail, bacterial enteric pathogens, Enterobacteriaceae, and sentani lake.